Modelling effective rheologies for viscoelastic porous media with application to silt, and medium coarse sand (2004)
A modification of Biot's poroelastic differential equations is made to include matrix-fluid interaction mechanisms which assume a solid-fluid relaxation function coupling coefficient. Values of physical properties of sediments are incorporated into equations which define phase velocity and attenuation for porous media which are dependent on the composite densities of various media (silt, and medium and coarse sand). The results enable us to compare the attenuation and velocities of waves in these media. We observed that the density of coarse sand is greater than that of medium sand and this in turn is greater than that of silt-the same holds-for the velocities of P-waves in these media but the situation is converse for shear waves in the same given media. As the densities of the media increase, their attenuation decreases as it was found that the attenuation of silt is the highest and that of coarse sand lowest for the media considered.